Stydy case of BIM applied to facility management = Estudio de caso de BIM aplicado a Facility Management (2019)
Purpose - The purpose of this paper is to show the results obtained by applying the theory behind Building Information Modeling (BIM) to Facility Management (FM) in a real-life project, specifically the Block C of the University of the Andes. Methodology - The methodology that was used to achieve this goal consist in three stages. First, an investigation of the current state of the art, where a research of the current practices around the world was made, as well as a recollection of the management practices in the Campus through interviews with the maintenance personnel. Secondly, a roadmap for the implementation of BIM in FM was evaluated by the application of the theory learned in the Block C. Finally, conclusions and recommendations for further progress in the field where made. Findings - The findings result in a better comprehension of how BIM can improve the maintenance process in a facility taking as an example the case of a university campus. Doubts about the process of implementation of BIM in facility management will be clarify as well. Originality/Value - As a very unexplored topic, the results compiled at the end of this paper pretend to contribute to the knowledge of BIM applications for Facility Management. Thereby, this paper presents a closer approach to the process of the implementation of BIM in the maintenance of a facility, as well as the the keys and barriers that need to be considered in order to achieve this goal.